Model Cognitive Stage Experiential (CSE) dan Kesadaran Dini Kebhinekatunggalikaan Siswa SD Kelas Rendah - Hambali, IM (Jurnal Kajian Bimbingan dan Konseling, 2016)
This research aims to determine: (1) the proportion of the level of awareness of diversity in the very low category; (2) the proportion of the level of awareness of diversity in the low category; (3) the proportion of the level of awareness of diversity in the medium category; (4) the proportion of the level of awareness of diversity in the high category; (5) the proportion of the level of awareness of diversity in the very high category. The research results show that: (1) the proportion of the level of awareness of diversity in the very low category is 42.5%, 43% and 41%; (2) the proportion of the level of awareness of diversity in the low category is 20%, 20%, 22%; (3) the proportion of the level of awareness of diversity in the medium category is 27%, 25%, and 26%; (4) the proportion of the level of awareness of diversity in the high category is 5%, 9%, 7%; (5) the proportion of the level of awareness of diversity in the very high category is 6%, 3%, 4%.